Platelet-Rich Plasma versus Corticosteroid Injection for the Treatment of Lateral Epicondylitis: A Systematic Review of Systematic Reviews - Jordyn A Kemp; Megan A Olson; Matthew A Tao; Christopher J Burcal (International Journal of Sports Physical Therapy)
# Background